Penyuluhan Penguatan Sumber Daya Manusia Bawaslu Kabupaten Merangin - Salman; Cantika, Fuji; Handayani, Fitri (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
Effective election supervision is crucial in ensuring honest, fair, and transparent elections. This study aims to improve the election supervisors' skills in Merangin Regency through counseling, simulations, and hands-on practice, as well as strengthening the ethics and integrity of supervisors in carrying out their duties. The method used in this community service is the provision of theoretical materials followed by election supervision simulations that depict various stages of the election process. Participants are also trained to understand the importance of maintaining ethics and integrity in every action they take. The results of this service show that simulations and hands-on practice enhance the technical skills of supervisors, while strengthening ethics and integrity bolsters supervisors' commitment to a fraud-free election. It is hoped that this activity can improve the quality of election supervision in Merangin Regency and create more credible and trusted elections in the community.